Color and Chemical Oxygen Demand Removal of Strobilanthes cusia Fermentation and Natural Indigo-based Batik Dyeing Wastewater - Kurniawan, Cepi; Mahatmanti, F. Widhi; Mahfudz, Johar; Qonita, Ulya; Nugraha, Rizki; Bahron, Hadariah (International Journal of Research Innovation and Entrepreneurship, 2021)
Strobilanthes cusia is the plant which has been cultivated at the District of Temanggung, Indonesia and used as a natural source for indigo dye. The use of natural dyes for Batik Industries are expected to prohibit environmental damage. However, the wastewater generated from the indigo extraction and Batik dyeing process is still showing high COD value (768-3.893 ppm). In the present study, color and COD removal from Strobilanthescusia processing (settling pond) and Indigo-based Batik dyeing (equalization tank) wastewater have been studied. The treatment involving the use of FeSO4, Alum, and Cyclea Barbata Miers. powder (CBM) as coagulation-flocculation agents. Alum was efficiently reduced color up to 97% and 93% for settling pond and equalization tank effluent, respectively. The highest COD removal efficiencies of 87 % and 63% were observed for settling pond and equalization tank effluent, respectively.